Combined nanofiltration and advanced oxidation processes with bifunctional carbon nanomembranes. Issue 24 (23rd April 2021) - Shapira, Barak; Penki, Tirupathi Rao; Cohen, Izaak; Elias, Yuval; Dalpke, Raphael; Beyer, André; Gölzhäuser, Armin; Avraham, Eran; Aurbach, Doron
Abstract : A proof of concept of bi-functional membrane, for wastewater treatment, consisting of partially reduced graphene oxide and CNM is demonstrated. Abstract : Wastewater reclamation is becoming a top global interest as population growth and rapid industrialization pose a major challenge that requires development of sustainable cost-effective technologies and strategies for wastewater treatment. Carbon nanomembranes (CNMs)—synthetic 2D carbon sheets—can be tailored chemically with specific surface functions and/or physically with nanopores of well-defined size as a strategy for multifunctional membrane design. Here, we explore a bifunctional design for combined secondary wastewater effluent treatment with dual action of membrane separation and advanced oxidation processes (AOP), exploiting dissolved oxygen. The bifunctional membrane consists of a CNM layer on top of a commercial ultrafiltration membrane (Microlon™) and a spray-coated reduced graphene oxide (rGO) thin film as the bottom layer. The CNM/support/rGO membrane was characterized by helium ion and atomic force microscopy, FTIR, XPS with a four-point conductivity probe, cyclic voltammetry, galvanostatic measurements, and impedance spectroscopy. Combined treatment of water by nanofiltration and AOP was demonstrated, employing a unique three electrode-dead end filtration setup that enables concurrent application of potential and pressure on the integrated membrane. For the model organic compound methylene blue, oxidation (by the Fenton reaction) was evaluated using UV-vis (610 nm). The rejection rate and permeability provided by the CNM layer were evaluated by dissolving polyethylene glycol (400 and 1000 Da) in the feed solution and applying pressure up to 1.5 bar. This demonstration of combined membrane separation and AOP using an integrated membrane opens up a new strategy for wastewater treatment.